Medicinal Plants Used in the Management of Skin Disorders in Kenya: A Review - Wanga, Lucy; Nyamboki, Divinah Kwamboka (Pharmacognosy Reviews)
Skin health has increasingly become a great aspect in primary health care globally especially with the increasing number of immunocompromised individuals and the worrying increase in antimicrobial resistance. In the low and middle income countries such as Kenya, the conditions are further exacerbated by poor living conditions and inadequate access to proper medical care. Different ethnic communities in Kenya use various plants to manage and alleviate symptoms of skin disorders. This research aimed to critically review the different medically important plants that have been used by different communities over the years to treat skin and soft tissue infections (SSTIs) and fungal infections as a source of alternative medicine. Scientific evaluation of some of the presented medicinal plants have also been summarized in this study. The information presented in this study was obtained from primary and review scientific studies and ethno-botanical books published until the year 2022 from the Google Scholar databases, Science Direct, AJOL, and PubMed. Atleast one hundred and eighteen Kenyan medicinal plant species from fifty families have been recorded for traditional medicinal therapies for various skin disorders. Scientific evidence of the medicinal importance of some of the listed plants have also been reported however, there is no clear scientific report on the toxicity of these medicinal plants. Alternative medicine is widely practiced in rural Kenya, however there is limited scientific knowledge that supports their ethno-botanical importance in the management of skin disorders. Hence substantial further research is recommended on the various medicinal plants listed in this study.
Keywords: Dermatophytosis; Skin infections; Medicnal plants